Using Task-Based Learning in CLT to Foster Engagement Among English Beginners in Pamulang University - Darmawati; Neneng Misliyah (CV. Shofanah Media Berkah, 2024)
This action research explores the implementation of Task-Based Learning (TBL) within the framework of Communicative Language Teaching (CLT) to enhance engagement among English beginners at Pamulang University. The study was conducted with a group of 25 first-semester Informatics Engineering students who had limited English proficiency. Using a qualitative approach, the research was carried out over two cycles, each involving the stages of planning, action, observation, and reflection. In the first cycle, task based activities such as role-playing, information gap tasks, and group discussions were introduced to encourage communication. Data collected through classroom observations, student reflections, and teacher journals indicated initial challenges, including hesitancy to participate and difficulty understanding instructions. Based on these findings, adjustments were made in the second cycle, including the use of scaffolding techniques, clearer task instructions, and the incorporation of multimedia resources to support vocabulary acquisition. The results showed a significant improvement in student engagement and willingness to participate in communicative tasks. Students reported increased confidence in using English and found the activities enjoyable and relevant to their academic needs. The study concludes that integrating TBL into CLT is an effective approach to fostering active participation and building communicative competence among English beginners. It also emphasizes the iterative nature of action research in refining teaching strategies to address learners' needs in specific contexts.